A Critical Analysis on Marital Rape: Recognizing Its Complexities and Addressing the Challenges - -, Sonia (International Journal For Multidisciplinary Research, 2025)
In the previous two to three decades, there has been an increase in marital rapes in India, despite the growing recognition of numerous penal laws. India needs a unique legislation on marital rape, which should be recognized by worldwide standards for this specific matter. Women have the legal and social right to fight for their protection, but in the end, it is not in his best interests to torment and injure her own husband—whom she married with complete confidence—by forcing them to have sex against their will. The idea of any form of marriage exemption is now without merit or relevance. This paper aims to make marital rape a crime, and it should be legalized for rape to be considered a crime in any form. Any forced sexual relations without the spouse's permission are a kind of rape. This research examines comparative studies and addresses the differentiation between marital and sexual rape. Various observations made by Indian courts on occasion in various cases have also been appropriately included in this study article. The study also discusses marital rape from a legal and societal standpoint. This includes a thorough discussion of the many varieties of marital rape, its devastating effects, and suitable strategies to address this grave issue.